Electrochemical investigation of the role of cl- on localized carbon dioxide corrosion behavior of mild steel - Jiang, X.; Nesic, S.; Kinsella, Brian; Brown, B.; Young, D. (NACE International, 2013)
Electrochemical behavior of localized carbon dioxide (CO2) corrosion of X65 mild steel at 80°C in 0.1, 1.0, 10, and 20 wt% sodium chloride (NaCl) solutions have been investigated using electrochemical techniques including linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS). Surface morphology of specimens was observed using scanning electron microscopy (SEM). Pit depth and its corresponding 3D optical measurement were undertaken using infinite focus microscopy (IFM). The results showed that Cl- concentration had only a slight effect on general corrosion rate. It also revealed that increasing Cl- concentration did not accelerate the initiation of localized corrosion; localized corrosion rate did not change with increasing NaCl solution concentrations; and chemical dissolution of corrosion product film could initiate localized CO 2 corrosion. © 2013, NACE International.